Distribution of Cobalt in Soil from Кavadarci and the Environs (Geologica Macedonica, 2013)
The results of the study of spatial distribution of cobalt in surface soil and subsoil over of the Kavadarci region, Republic of Macedonia, are reported. From the investigated region (360 km2) in total 344 soil samples from 172 locations were collected. At each sampling point soil samples were collected at two depths, topsoil (0–5 cm) and subsoil soil (20–30 cm). Inductively coupled plasma – mass spectrometry (ICP-MS) was applied for the determination of cobalt. Data analysis and construction of the map were performed using the Paradox (ver. 9), Statistica (ver. 6.1), AutoDesk Map (ver. 2008) and Surfer (ver. 8.09) software. It was found that for both topsoil and subsoil the median and average values are 15 mg/kg, ranges between 6.7 and 58 mg/kg. The highest content of cobalt is present in the soil from the area of Paleozoic and Mesozoic rocks (Pz-Mz) on the western part of the investigated area and Flysch (E) – Eocene upper flysch zone (on the northern part) and the lowest in the soils from the Holocene alluvium of the rivers Crna Reka and Vardar. There are no significant differences between the surface and subsoil in terms of its average quantities. It was found that the critically high contents are related primarily to high contents of cobalt in the sampling points from the western part of the investigated region. The contents of cobalt are higher in subsoil than in topsoil from which it can be concluded that the occurrence is natural.